2006
DOI: 10.1523/jneurosci.4939-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of the Main Olfactory System in Social Recognition of Major Histocompatibility Complex Peptide Ligands

Abstract: Genes of the major histocompatibility complex (MHC),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
204
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(212 citation statements)
references
References 45 publications
(73 reference statements)
6
204
0
1
Order By: Relevance
“…Genotype discrimination via these peptides could be evolutionarily advantageous in a variety of processes ranging from assortative and disassortative mating to sympatric speciation. Importantly, SAV peptides will provide a signature of genomic individuality also in species lacking MUP polymorphism (for example, M. macedonicus) and, because peptides can additionally be detected by the main olfactory epithelium 22 , they may even play a role in species lacking a VNO. Despite all the differences in urinary peptides, one should be aware that, when comparing two given strains of M. musculus, most urinary peptides are shared (for example, our MS analyses showed that at least 70% of peptides identified in B6 mice were also present in BALB/c mice).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotype discrimination via these peptides could be evolutionarily advantageous in a variety of processes ranging from assortative and disassortative mating to sympatric speciation. Importantly, SAV peptides will provide a signature of genomic individuality also in species lacking MUP polymorphism (for example, M. macedonicus) and, because peptides can additionally be detected by the main olfactory epithelium 22 , they may even play a role in species lacking a VNO. Despite all the differences in urinary peptides, one should be aware that, when comparing two given strains of M. musculus, most urinary peptides are shared (for example, our MS analyses showed that at least 70% of peptides identified in B6 mice were also present in BALB/c mice).…”
Section: Discussionmentioning
confidence: 99%
“…This immunological signature must be interpreted by the olfactory system. It is now well established that, in freely behaving mice, nonvolatile peptides gain access to sensory neurons of both the main olfactory system and the VNO during behavioural situations involving direct physical contact 21,22 , that such peptides are powerful ligands for subsets of vomeronasal and olfactory sensory neurons [21][22][23][24][25] (VSNs and OSNs, respectively), that they induce brain activity downstream from the sensory neurons in vivo 26 , and that synthetic MHC peptide ligands can be discriminated in social preference tests 22 and influence social learning and reproductive function in the context of the Bruce effect test 21 . However, it is important to note that there is also considerable evidence for the use of MHC-independent, individual identity signatures in mice in specific behavioural contexts 27,28 (but see the discussion in Ruff et al 29 ).…”
mentioning
confidence: 99%
“…According to Wysocki et al (1980), the vomeronasal organ (VNO), but not the olfactory epithelium (with few exceptions, see Spehr et al, 2006), is able to detect non-volatile chemicals in the environment. Therefore, irrespective of the existence of volatile sexually attractive male pheromones, non-volatile male pheromones are detected by the VNO of females in which they elicit attraction and other behavioural responses.…”
Section: A Volatile Male Sexual Pheromones: Chemical Species and Thementioning
confidence: 99%
“…These functions were seen as being the exclusive domain of each sensory system, however as discussed above it is not only non-volatile compounds that act as pheromones in mammals [6], and recent evidence suggests that while there are functional differences between the two systems, there is also overlap between the two olfactory systems in their roles in pheromone detection. Both the VNO and MOE have recently been shown to respond to certain volatile odours [87] while MOE sensory neurons have also been shown to be activated by involatile peptides which were previously thought to be detected solely through the VNO [78]. These data indicate that the two olfactory systems do not operate in mutually exclusive sensory domains, however the majority of pheromonal effects in mammals are still thought to be mediated via the VNO [11] and it is only the MOE that has both the appropriate morphology and the complexity of sensory receptor to act as a chemosensor for general airborne odours.…”
Section: Pheromone Detectionmentioning
confidence: 99%
“…Recent electrophysiological work has shown that the volatile male mouse pheromone (methylthio)methanethiol clear responses in the MOB of female mice, indicating that the main olfactory system may mediate the attraction of females to this pheromone in mice [59]. Some pheromonal signals may also be processed in parallel by the two olfactory systems, as calcium imaging studies with nasal tissue slices have shown that there are sensory neurons that respond to MHC peptides in both the VNO and the MOE [78]. Evidence at both the behavioural and cellular level shows that some pheromones are detected by the MOE and processed by the main olfactory system leading to increasing questioning of the view that pheromonal communication in mammals is the exclusive preserve of the vomeronasal system [6].…”
Section: The Main Olfactory System and Pheromonesmentioning
confidence: 99%